P58 An audit of treatment outcomes for patients with tuberculosis diagnosed at an inner London teaching hospital between 2000 and 2010. (19th November 2012) - Togun, E; Stephens, S; Sewo, O; Perrin, FM; Barker, RD
Abstract : Background: The WHO has the ambition that 85% of patients starting treatment for TB achieve treatment success (cure or treatment complete). 1 There has been considerable anxiety that poor treatment completion rates would lead to increased transmission of tuberculosis and perhaps drive increased drug resistance. We have been monitoring treatment outcomes for patients registering at our hospital since the year 2000. Here we report outcomes and analyse risk factors for treatment interruption for patients with tuberculosis registering up until 2010. Methods: All patients diagnosed with tuberculosis at an inner London teaching hospital between 2000 and 2010 were included in the study. Outcomes were recorded, as defined by the requirements of the London TB Register. Follow-up of patients is predominantly nurse-led with little day-to-day involvement from doctors. Samples are sent to the National Mycobacterial Reference Laboratory – Whitechapel, for culture and sensitivity testing with first line anti-tuberculous drugs. Sex, Age (Decade), HIV status, disease site (pulmonary or extra pulmonary) and resistance to any first line drug were evaluated to see whether they were associated with "ost to follow up", as opposed to all other outcomes, using chi-square test for proportions. Results: One thousand two hundred and forty two patients were identified. Ten patients (1%) had MDRTB, 714 58% were male, 981 (79%) were born abroad, 160 (13%) aged 0–20 years, 679 (55%) 21–40 years, 279 22% (41–60), 124 10% > 60, 164 (13%) were known to be HIV, 596 (48%) had pulmonary disease 147 (18%) of 803 with positive cultures had any drug resistance. None of the variables assessed were significantly associated with being lost to follow up. Discussion: Our nurse led TB programme has resulted in outcomes that meet international standards. Less than 5% of patients interrupt treatment. The results would probably improve if we obtained treatment outcomes for those who transferred out. None of the variables examined should be used as indicators for enhanced supervision. World Health Organization - Stop TB Partnership. The Stop TB Strategy, 2006.